Mass spectrometric behavior of anabolic androgenic steroids using gas chromatography coupled to atmospheric pressure chemical ionization source. Part I: Ionization. (21st May 2014) - Raro, M.; Portolés, T.; Sancho, J. V.; Pitarch, E.; Hernández, F.; Marcos, J.; Ventura, R.; Gómez, C.; Segura, J.; Pozo, O. J.
<x xml:space="preserve">Abstract</x> The detection of anabolic androgenic steroids (AAS) is one of the most important topics in doping control analysis. Gas chromatography coupled to (tandem) mass spectrometry (GC–MS(/MS)) with electron ionization and liquid chromatography coupled to tandem mass spectrometry have been traditionally applied for this purpose. However, both approaches still have important limitations, and, therefore, detection of all AAS is currently afforded by the combination of these strategies. Alternative ionization techniques can minimize these drawbacks and help in the implementation of a single method for the detection of AAS. In the present work, a new atmospheric pressure chemical ionization (APCI) source commercialized for gas chromatography coupled to a quadrupole time‐of‐flight analyzer has been tested to evaluate the ionization of 60 model AAS. Underivatized and trimethylsylil (TMS)‐derivatized compounds have been investigated. The use of GC–APCI–MS allowed for the ionization of all AAS assayed irrespective of their structure. The presence of water in the source as modifier promoted the formation of protonated molecules ([M+H]+), becoming the base peak of the spectrum for the majority of studied compounds. Under these conditions, [M+H]+, [M+H‐H2O]+ and [M+H‐2·H2O]+ for underivatized AAS and [M+H]+, [M+H‐TMSOH]+ and [M+H‐2·TMSOH]+ for TMS‐derivatized AAS were observed as main ions in the spectra. The formed ions preserve the intact steroid skeleton, and, therefore, they might be used as specific precursors in MS/MS‐based methods. Additionally, a relationship between the relative abundance of these ions and the AAS structure has been established. This relationship might be useful in the structural elucidation of unknown metabolites. Copyright © 2014 John Wiley & Sons, Ltd.